To photodeprotect or not: effect of the oxidation state of the sulfur atom of thiochromone derivatives. Issue 83 (3rd October 2022) - Li, Xuyang; Guo, Yan; Xu, Tongyu; Wang, Jialin; Dai, Mingdong; Kakiuchi, Kiyomi; Morimoto, Tsumoru; Ma, Jiani
Abstract : Time-resolved spectroscopic experiments, assisted with DFT calculations, were employed to study the photochemical reaction mechanism of TC and TS-PPG in different solvents. Abstract : Time-resolved spectroscopic experiments, assisted with DFT calculations, were employed to study the photochemical reaction mechanism of (4-oxo-3-phenyl-4 H -thiochromen-2-yl) methoxycarbonyl-caged ethanol (TC) and (1, 1-dioxido-4-oxo-3-phenyl-4 H -thiochromen-2-yl) methoxy carbonyl-caged ethanol (TS-PPG) in different solvents. TC went through an intersystem crossing to form the triplet state with π–π* character in acetonitrile (MeCN) and protic solvents. While the n–π* triplet state was generated for TS-PPG in MeCN, which further underwent Paternò–Büchi reaction to give a biradical intermediate. Then, the C–O bond was cleaved, followed by deprotonation. Besides the similar deprotection route in MeCN, another reaction pathway existed in protic solvents, where the C–O bond heterolysis took place via the singlet excited state. The unambiguous mechanism would not only guide the efficient application of TS-PPG, but also help develop more excellent PPGs based on the thiochromone framework.